Hypertension secrets - Lerma, Edgar V.; Luther, James M. (Philadelphia, PA : Elsevier, 2023)
For more than 30 years, the highly regarded Secrets Series?? has provided students and practitioners in all areas of health care with concise, focused, and engaging resources for quick reference and exam review. Hypertension Secrets, 2nd Edition, offers practical, up-to-date coverage of the full range of essential topics in this dynamic field. This highly regarded resource features the Secrets' popular question-and-answer format that also includes lists, tables, pearls, memory aids, and an easy-to-read style - making inquiry, reference, and review quick, easy, and enjoyable.
Measurement of blood pressure in the office -- Ambulatory and home blood pressure monitoring -- Clinical evaluation of the patient with hypertension -- Hypertensive emergencies and urgencies -- The epidemiology of hypertension -- Physiology of blood pressure regulation -- Target organ damage or why should we treat hypertension? -- Primary aldosteronism and mineralocorticoid hypertension -- Glucocorticoid hypertension -- Pheochromocytoma and paraganglioma -- Other endocrine causes of hypertension -- Renovascular hypertension -- Drug-induced hypertension -- Obstructive sleep apnea and hypertension -- Hereditary causes of hypertension -- Hypertension in children and adolescents -- Hypertension in chronic kidney disease and end-stage kidney disease -- Hypertension in diabetes -- Hypertension after transplantation -- Treatment of hypertension in obesity -- Hypertension in blacks -- Hypertension in the elderly -- Hypertension in pregnancy -- Hypertension in heart disease -- Hypertension in stroke -- Hypertension in the patient with aortic dissection -- Resistant and pseudoresistant hypertension -- Hyperkalemia in hypertension -- Lifestyle modifications for hypertension management -- Blood pressure treatment goals -- Angiotensin-converting enzyme inhibitors and angiotensin receptor blocker -- Calcium channel blockers -- Direct vasodilators -- Loop and thiazide diuretics -- Potassium-sparing diuretics -- Alpha antagonists -- Beta-blockers -- Alpha-agonists -- Drug-drug and pharmacogenetic interactions -- Role of device therapy -- Orthostatic hypotension -- Baroreflex dysfunction -- Hypertension: origins.
Includes bibliographical references and index.
Keywords: Hypertension